Characterization of Indian type ’0’ foot-andÂ·mouth-disease virus isolates using polyclonal and monoclonal antibodies - TOSH, C; PATTNAIK, B; VENKATARAMANAN, R (The Indian Journal of Animal Sciences, 2013)
Twelve neutralizing monoctonal antibodies (Mabs) to the type ’0’ foot-and-mouth disease vaccine virus strain (R2/15) were used for characterizing 21 type ’0’ field isolates in enzyme-linked immunosorbent assay (ELISA). The results obtained with Mabs were compared with those obtained with comp!lement. fixation test, sandwich ELISA and 2-dimensional microneutralization test using polyclonal antibodies. The combined study revealed serological relatedness of all the field isolates with the reference virus.